2019
DOI: 10.3329/medtoday.v31i1.40313
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Sutureless and Glue Free versus Sutured Limbal Conjunctival Autograft in Primary Pterygium Surgery

Abstract: Introduction: To compare and evaluate the safety and efficacy of two surgical techniques for the management of primary pterygium. Materials & Methods: The study included 176 eyes of 176 patients with primary pterygium. The mean age was 49 ± 12 years (range 24–74 years). Simple excision under local anesthesia was performed followed by closure of the bare sclera by suture less and glue free conjunctival autograft in 76 eyes of 76 patients (group 1), versus the conventional method of a sutured conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Our study had lesser dehiscence than a study done by Elwan (2014) where 8% cases had graft dehiscence in the sutureless group. Its incidence was low in the sutureless group (1.3%) in a study done by Huda and Khaleque, (2019).…”
Section: Discussionmentioning
confidence: 86%
“…Our study had lesser dehiscence than a study done by Elwan (2014) where 8% cases had graft dehiscence in the sutureless group. Its incidence was low in the sutureless group (1.3%) in a study done by Huda and Khaleque, (2019).…”
Section: Discussionmentioning
confidence: 86%
“…[6] Bare sclera excision is no more used nowadays as it has an unacceptably high recurrence rate ranging from 24% to as high as 89% and has become obsolete. [7] Postoperative beta irradiation to the bare sclera has been in use for decades and led to reduction in recurrence associated with bare sclera technique. However complications of beta irradiation limit its use.…”
Section: Discussionmentioning
confidence: 99%
“…The study selection process is shown in Figure 1. RCTs were used in the nine studies [7], [14], [15], [16], [17], [18], [19], [20], [21] that matched the inclusion criteria. Table 1 lists the characteristics of the nine studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The risk of bias in each included study shown in Figure 2. All nine studies did randomization, but six studies [7], [14], [16], [17], [19], [20] have a low risk of bias in the "random sequence generation" parameter by elaborating the randomization method. Two studies [20], [21] did not explain the randomization method, and one study [18] had a high risk of bias assessment in this parameter.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation